Optics: Watch your back - K. L. Tsakmakidis; Hess, O. (Nature, 2008)
A proposal for transporting photons invisibly between two unconnected points in space seems worthy of a Star Trek plot. But it is in principle wholly realizable, and could open up new vistas - literally. ©2008 Nature Publishing Group.
cited By 7